2017
DOI: 10.1002/fsn3.508
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thermal processing on the nutritional and functional properties of defatted conophor nut (Tetracarpidium conophorum) flour and protein isolates

Abstract: Conophor nut (Tetracarpidium conophorum) was processed using different heat treatments to explore its full potential as food ingredients. The raw, boiled, and toasted nuts were defatted and the proteins isolated by alkaline solubilization and isoelectric precipitation. The variously processed nuts were analyzed for the proximate and amino acid compositions, and functional properties. The protein contents of the isolate ranges between 86.86 g/100g and 87.74 g/100 g, about 1.5‐fold higher than those of the defat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 54 publications
(76 reference statements)
2
12
1
Order By: Relevance
“…It decreased progressively with increasing cooking time (Table 3) and ranged from 2.05 to 2.72. These values compare well with the values (2.39-2.60) reported for Conophor protein isolates (Iyenagbe et al, 2017). The P-PER of the plant foods at all levels of processing was higher than 1.50, below which a protein is taken to be of low or poor quality (Friedman, 1996).…”
Section: The Effect Of Thermal Processing On Protein Quality Parameterssupporting
confidence: 87%
See 1 more Smart Citation
“…It decreased progressively with increasing cooking time (Table 3) and ranged from 2.05 to 2.72. These values compare well with the values (2.39-2.60) reported for Conophor protein isolates (Iyenagbe et al, 2017). The P-PER of the plant foods at all levels of processing was higher than 1.50, below which a protein is taken to be of low or poor quality (Friedman, 1996).…”
Section: The Effect Of Thermal Processing On Protein Quality Parameterssupporting
confidence: 87%
“…Lastly, Glycine was increased by 1.4% (R10), 2.4% (R20), and 8.1% (R30) respectively. Iyenagbe et al (2017) reported increases of up to 18.85%, 33.5%, and 37.5% in the glycine, tryptophan, and histidine, respectively, for protein isolates of processed conophor nut (Tetracarpidium conophorum) samples. The effect of boiling on the amino acid content of Monodora myristica seeds was more noticeable when the degree of reductions for the individual amino acids was considered.…”
Section: The Effect Of Thermal Processing On the Concentration Of Amimentioning
confidence: 99%
“…increased water absorption of sorrel seed flour from 115% to a range of 165% -266%; with highest increase in roasted seed flour (ROSF) and the lowest in DDSF. Iyenagbe et al [50] reported similar higher increase of WAC in toasted conophor seed flour. This increase may be due to protein denaturation which occurs during heat processing, resulting in increased WAC [50].…”
Section: Water and Oil Absorption Capacities And Swelling Powermentioning
confidence: 80%
“…Iyenagbe et al [50] reported similar higher increase of WAC in toasted conophor seed flour. This increase may be due to protein denaturation which occurs during heat processing, resulting in increased WAC [50]. Also, increased protein content reported earlier in this study (Subsection 3.1) may account for increased WAC since proteins have the ability to absorb and retain water [61].…”
Section: Water and Oil Absorption Capacities And Swelling Powermentioning
confidence: 80%
“…This was considered typical of high‐quality proteins, whereby low‐quality proteins have PER values below 1.50 (Friedman, ). The PER values recorded were predominantly higher than those of conophor nut (2.39–2.60), lupin (2.22–2.34), and Vicia faba (2.60–2.90) protein isolates (El‐Adawy, Rahma, El‐Bedawey, & Gafar, ; Iyenagbe, Malomo, Idowu, Badejo, & Fagbemi, ; Vioque et al, ).…”
Section: Resultsmentioning
confidence: 95%